Modulation of K2P2.1 and K2P10.1 K+ channel sensitivity to carvedilol by alternative mRNA translation initiation. (28th August 2014) - Kisselbach, J; Seyler, C; Schweizer, P A; Gerstberger, R; Becker, R; Katus, H A; Thomas, D
<x xml:space="preserve">Abstract</x> Background and Purpose The β‐receptor antagonist carvedilol blocks a range of ion channels. K2P2.1 (TREK1) and K2P10.1 (TREK2) channels are expressed in the heart and regulated by alternative translation initiation (ATI) of their mRNA, producing functionally distinct channel variants. The first objective was to investigate acute effects of carvedilol on human K2P2.1 and K2P10.1 channels. Second, we sought to study ATI‐dependent modulation of K2P K+ current sensitivity to carvedilol. Experimental Approach Using standard electrophysiological techniques, we recorded currents from wild‐type and mutant K2P2.1 and K2P10.1 channels in Xenopus oocytes and HEK 293 cells. Key Results Carvedilol concentration‐dependently inhibited K2P2.1 channels (IC50, oocytes = 20.3 μM; IC50, HEK = 1.6 μM) and this inhibition was frequency‐independent. When K2P2.1 isoforms generated by ATI were studied separately in oocytes, the IC50 value for carvedilol inhibition of full‐length channels (16.5 μM) was almost 5‐fold less than that for the truncated channel variant (IC50 = 79.0 μM). Similarly, the related K2P10.1 channels were blocked by carvedilol (IC50, oocytes = 24.0 μM; IC50, HEK = 7.6 μM) and subject to ATI‐dependent modulation of drug sensitivity. Conclusions and Implications Carvedilol targets K2P2.1 and K2P10.1 K+ channels. This previously unrecognized mechanism supports a general role of cardiac K2P channels as antiarrhythmic drug targets. Furthermore, the work reveals that the sensitivity of the cardiac ion channels K2P2.1 and K2P10.1 to block was modulated by alternative mRNA translation initiation.